Documenting Value Creation: A Business Opportunity for Architects, Their Clients and Society. (2nd July 2020) - Sattrup, Peter Andreas
Abstract: Architects have often neglected documenting the value of architectural design in terms their stakeholders understand, with detrimental effects on their fees and the esteem of their profession. But there are ways forward. Architect Peter Andreas Sattrup, Senior Advisor on Sustainability for the Danish Association of Architectural Firms, explains the association's framework for value creation by architectural design and how it can open up new business opportunities.